نحو دور للسياسات التجارية في حـماية البيئة وتحقيق التنمية المستدامة مع الإشارة إلى حالة الاتحاد الأوروبي - بالحبيب, عبد الكامل (جامعة الوادي - University of Eloued, 2017)
تزايد الاهتمام العالمي بقضايا البيئة والمشاكل التي تعاني منها،هذا الاهتمام ركزعلى عدة جوانب منها الأسباب ومظاهر تدهور البيئة، والنتائج، وكذا محاولة تقديم عدة حلول للحد من الظاهرة، كل حسب وجهة نظره، وكثيرون أرجعوا سبب التدهور البيئي إلى النمو في النشاط الاقتصادي؛حيث يتناول هذا البحث العلاقة بين كل من السياسات التجارية والتنمية المستدامة من خلال البعد البيئي، بدءا بالتأصيل النظري للعلاقة بين نشاط التجارة الدولية والبيئة والآراء المختلفة حول التأثير الإيجابي والسلبي وكذا مفهوم التنمية المستدامة، إضافة إلى حماية البيئة في ظل الاتفاقيات الدولية، والمنظمة العالمية للتجارة، وكذا جهودها لاحتواء الآثار السلبية الممكنة لتحرير التجارة على البيئة العالمية، كما تناول البحث موضوع إدراج المعايير البيئية كأدوات للسياسة التجارية، من أجل جعل نشاط التجارة الدولية يهدف إلى المحافظة على البيئة وترقيتها، حيث ركزنا على معيار إيزو 14001 والمواصفات الأوروبية EMAS . The global concern about the issues and the problems of ecology has increased. This concern focuses on many points as causes and aspects of ecological deterioration , its results and attempts to find solutions to this phenomenon . There are many points of view, but many people think that the reason behind the environmental degradation is the economic activity. This research deals with the link between trade policies and sustainable development in relation to the ecological dimension starting with the theoretical rooting of the relation between the activity of the international trade and ecology; the different opinions about the positive and the negative influence , the definition of sustainable development , the preservation of ecology considering the international conventions and World Trade Organization as well as its efforts to diminish the negative effects of world trade liberalization on global ecology. Also this research tackles the insertion of the ecological standards as tools for trade policy in order to make the activity of international trade aims at preserving and promoting ecology focusing on ISO s standard 14001 as well as the European standard EMAS
Towards a role for trade policies in protection of the environment and achieving sustainable development with reference to the European Union
مقال بمجلة الدراسات المالية والمحاسبية . مج 08 ع01. جوان 2017 . جامعة الوادي
Keywords: السياسات التجارية، البيئة، التنمية المستدامة، الاتحادالأوروبي; trade policies, environment, sustainable development, European Union